Clan culture and internal pay gap: Evidence from listed family firms - Guoyiming Zhu; Guangyong Lei; Jingjing Zuo (China Journal of Accounting Studies (CJAS), 2023)
Clan culture, as an enduring traditional culture in China, has a profound impact on the internal governance and sustainable development of family firms. This study reveals a significant positive relationship between regional clan culture and the pay gap within family firms. This relationship is primarily realised through the mechanism of internal trust. Moreover, the positive relationship is more pronounced in firms with local executives, same-name executives, and family members, as well as in regions with high marketing intensity, a thriving economic environment, and openness to the outside world. The study also suggests that the pay gap resulting from clan culture reinforces the conservative impact on the performance, market value, and productivity of family firms in economic sequences. By highlighting the negative effects of clan culture on family business, this research contributes to the literature on corporate governance within a cultural framework.
Keywords: 650; Information institution; clanculture; family firms; internalpay gap; internal trust